1994
DOI: 10.1109/42.310874
|View full text |Cite
|
Sign up to set email alerts
|

Bandlimited and Haar filtered back-projection reconstructions

Abstract: A new way to discretize the filtered back-projection (FBP) algorithm is presented. The function basis is the Haar system (2D product of rectangular windows). This scheme allows one to derive the optimal shape of the apodisation window, which is angle varying, and the oversampling ratio between the pixel and the projection cell size. The discrete equivalent filter is also derived. The comparison of standard radial band-limited and separable Haar reconstructions shows that improvements, in terms of linearity, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In the FBP literature [18], the customary rule is to use four-times over-sampling on the sinogram and twice as many angles as the size of the image along one dimension. Our experiments refines this rule and suggests similar rules for higher approximation orders.…”
Section: E Fbp: Angular Resolution Versus Sinogram Sampling Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FBP literature [18], the customary rule is to use four-times over-sampling on the sinogram and twice as many angles as the size of the image along one dimension. Our experiments refines this rule and suggests similar rules for higher approximation orders.…”
Section: E Fbp: Angular Resolution Versus Sinogram Sampling Stepmentioning
confidence: 99%
“…Even though the standard implementation uses a rather rudimentary discretization-at least by modern standards, it has not been much improved over the years, except for the aspect of filter design [17]. One noteworthy exception is the work of Guédon et al who derived an optimal reconstruction filter based on a piecewise-constant model of the image [18]. Some wavelet approaches can also be viewed as multi-scale variations on FBP [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…This correspondance has been applied for the continuous and discrete Radon transforms defined into spline spaces leading to new filtered backprojection algorithms [7,8].…”
Section: Related Workmentioning
confidence: 99%
“…Guédon et al [1] have shown that the standard FBP could be improved by using an explicit piecewise constant model of the image with basis functions that are B-splines of degree n = 0. Here, we will use our B-spline convolution kernels to extend the approach to higher-order splines.…”
Section: Spline-based Radon Transform and Filtered Back-projectionmentioning
confidence: 99%
“…B-splines basis functions are well suited for this kind of computation [7]. In particular, they have been applied to the problems of image resizing [2], [4], [8] and to tomographic reconstruction by filtered back-projection [1], [3]. The main difficulty of the above-mentioned algorithms is that they involve the computation of inner products (or continuously-defined convolutions) of B-splines of different widths.…”
Section: Introductionmentioning
confidence: 99%